Autonomia universitária e a regularização de atos escolares - Cioccari, Lauricio Antônio (2010)
This paper analyzes the process of validation of the student’s work in high school, undergraduate and graduate programs in the context of the private university’s autonomy to decide what to consider valid. The registration of activities related to the courses, workload, course requirements, tests and credit for work done at other institutions is of paramount importance to the trajectory of the student in the university, and the continuity of his education and professional life. Vices such as deletions, omissions, discrepancies and other illegalities, may invalidate the certificate of completion of high school, which requires convalidation by the authorized organization (Municipal or State Education) or the diplomas of undergraduate or graduate studies ( MA and PhD), which require their convalidation by the National Council of Education. From a theoretical framework, we discuss the concepts of the university as an institution, its administrative, financial, scientific and didactic ativities; regularization of studies, convalidation studies of high school, higher education (undergraduate and graduate) and revalidation of diplomas (of undergraduate and graduate studies) and others, in the context of private university and, in particular, the limits of autonomy with regard to the process and results of the questions raised. The qualitative research, resulted in the collection of several cases of validation of studies, judicial decisions and opinions of the then Federal Council of Education, National Council of Education today. Such opinions recommend avoiding the arguments in good faith, a fait accomplished and the course of time, for greater smoothness and legal reasoning processes. The private university, evaluated regularly by the governing bodies, re-credentialed after each evaluation cycle, it could assume, among its competencies, the assignment to validate the studies of high school and college, and revalidation of diplomas of undergraduate and graduate studies. Call back to validate the act of studies from basic guidelines issued by the Ministry of Education, and with all seriousness that the case requires, the University gives agility to the process and somehow vent the flow of cases referred to that body